2007
DOI: 10.1111/j.1540-8167.2007.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and Pharmacological Responses of Idiopathic Ventricular Tachycardia Arising from the Left Ventricular Outflow Tract

Abstract: The results suggest that the mechanism of VT from LVOT is mostly due to cAMP-mediated triggered activity as similar to that in VT from RVOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…The RVOT VAs present with a distinct ECG pattern of left bundle branch block and inferior axis (Fig. 2) (23)(24)(25)(26). In general, LVOT VAs manifest an early precordial R-wave transition (in V 2 or V 3 ) because of its more posterior location compared with the RVOT (Fig.…”
Section: Non-life-threatening Ventricular Arrhythmias Typically Monomentioning
confidence: 97%
See 1 more Smart Citation
“…The RVOT VAs present with a distinct ECG pattern of left bundle branch block and inferior axis (Fig. 2) (23)(24)(25)(26). In general, LVOT VAs manifest an early precordial R-wave transition (in V 2 or V 3 ) because of its more posterior location compared with the RVOT (Fig.…”
Section: Non-life-threatening Ventricular Arrhythmias Typically Monomentioning
confidence: 97%
“…ELECTROPHYSIOLOGIC MECHANISM. It is well established that outflow tract arrhythmia (OTA) is due to triggered activity secondary to cyclic adenosine monophosphatemediated delayed after depolarizations (23,24,27,28). Increased cyclic adenosine monophosphate due to betaadrenergic receptor stimulation, for example, with exertion, results in release of calcium from the sarcoplasmic reticulum and delayed afterdepolarizations.…”
Section: Non-life-threatening Ventricular Arrhythmias Typically Monomentioning
confidence: 99%
“…A transient inward (ITi) current and corresponding DAD are generated from the Na + -Ca 2+ exchanger. 23 Moreover, Yamawake et al investigated the vagal stimulation and pharmacological responses of I-VA arising from the LVOT and suggested that the mechanism of the LVOT-VA was mostly due to cAMPmediated triggered activity, similar to that of RVOT-VA. 24 However, the mechanism of left-sided I-VA might be not only DAD but also re-entry. 25 This is because sometimes discrete sharp potentials were recorded at the ablation site of the left-sided VA. 26 The pathological mechanisms for gender related differences in I-VA remains unknown.…”
Section: Gender and Age Differencesmentioning
confidence: 99%
“…Az idiopathiás VT-k mechanizmusa fokális automácián vagy többnyire triggerelt aktivitáson alapul. Ez utóbbi magas intracelluláris Ca²-koncentrációhoz és ezáltal elhúzódó utódepo-larizációhoz vezet [29]. Ez megmagyarázza a ritmuszavar indulását fi zikai aktivitás során vagy isoproterenol adását követően.…”
Section: Idiopathiás Vt-k Ablatiójaunclassified